Angiosarcoma of the breast: a case report - Andrikou, Kalliopi; Triggiani, Edoardo; Rossiello, Maria Rosaria; Didone, Nicola; Teodossiu, Giovanni (European Journal of Oncology and Environmental Health, 2009)
Angiosarcoma of the breast is a rare and highly aggressive vascular cancer. Here we describe a case of a 36-year-old woman with angiosarcoma of the left breast who presented with breast enlargement and a bluish red discoloration in the overlying skin. The mammographic and sonographic findings were aspecific and due to the color doppler findings and the discoloration of the overlying skin, an angiosarcoma was suspected. A biopsy of the area identified at the color doppler sonography was performed and the histological examination showed the presence of a low-grade angiosarcoma. Systemic examinations (CT, total body bone scintigraphy) showed no evidence of metastasis. A left modified radical mastectomy was performed and pathological examination confirmed the presence of a grade I angiosarcoma. Immunohistochemistry showed that the neoplastic cells were positive for factor VIII, CD 31 and CD 34 confirming the tumor vascular origin. The patient presents no evidence of disease 3 years after surgery.